Unexplained Cardiac Uptake on 99mTc-MDP Bone Scan in a Patient with Prostate Cancer - Malik Juweid; Baraa AlSyouf; Nour Kasasbeh; Waleed Mahafza; Serin Moghrabi; Hanna Al-Makhamreh; Akram Saleh (Asia Oceania Journal of Nuclear Medicine and Biology)
This case report presents a case of unusual diffuse cardiac uptake (Peruguni 3: uptake greater than rib uptake) on a 99mTc-methylene diphosphonate bone scan in an 83-year-old patient with metastatic prostate cancer which is almost resolved (Peruguni 1: uptake less than rib uptake) on a follow up bone scan about 4.4 months later.  Laboratory values and imaging were negative for cardiac amyloidosis and a thorough review of the patient's medical chart did not reveal any other possible causes, pharmacologic or otherwise, thus deeming the uptake non-specific. While increased non-specific cardiac 99mTc-diphosphanate uptake has been previously reported in elderly prostate cancer patients, possibly attributable to asymptomatic atherosclerosis, this explanation is unlikely considering that the uptake almost resolved within a relatively short period of time. It is clinically important to rule out amyloidosis in patients with increased cardiac uptake on bone scans. However, we believe that clinicians should also consider the possibility of non-specific uptake as a cause for cardiac uptake on bone scan, which would only require follow-up rather than medical intervention.